Analisis Kritis Pembiayaan Murābaḥah di Keuangan Islam Modern Indonesia - Ahmad Maulidizen (Jurnal Ilmiah Ekonomi Islam, 2018)
Islamic banking in Indonesia has experienced significant growth, including assets, financing provided and the number of customers. In 2012-2017 Sharia bank financing 70-80% is given to the community by using the contract of murābaḥah, in the form of consumptive and productive. The activities of sharia banks should be guided by the National Sharia Council Fatwa in performing its functions optimally and implementing the Shari'a comprehensively. While murābaḥah financing is still reaping a variety of criticism from Islamic finance experts because there are provisions that are not in accordance with fiqh muamalat and also need to find solutions how to calculate the price and mark up allowed so that customers do not burden at a cost much more expensive than the interest applied in conventional banks. This is so that Sharia banks can compete with other banks. Therefore, this article will explain concept concept of murābaḥah conceptually and application in Bank Islam in Indonesia. The purpose of writing this article so that the implementation of the contract murābaḥah in Bank Syariah in Indonesia can be in accordance with the principles of sharia that put forward the principle of justice and no party is harmed. Saran sitasi: Maulidizen, A. (2018). Analisis Kritis Pembiayaan Murābaḥah di Keuangan Islam Modern Indonesia. Jurnal Ilmiah Ekonomi Islam, 4(2), 76-90. doi:http://dx.doi.org/10.29040/jiei.v4i2.189